2002
DOI: 10.1023/a:1014256707875
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Genomic research on target identification and validation has created a great need for methods that rapidly provide detailed structural information on protein-ligand interactions. We developed a suite of NMR experiments as rapid and efficient tools to provide descriptive structural information on protein-ligand complexes. The methods work with large proteins and in particular cases also without the need for a complete three-dimensional structure. We will show applications with two tetrameric enzymes of 120 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
1
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 15 publications
0
85
1
1
Order By: Relevance
“…Although the fluorescence-based assay is a robust technique to search for very potent inhibitors, it becomes more ambiguous in detecting weaker ligands (Ͼ100 M), possibly due to interference introduced by test compounds (normally used at high concentration) in the spectrophotometric assay. For this reason, we relied on a NMR-based enzymatic assay, which is unlikely to lead to false positives (16)(17)(18)(19)(20)(21)(22)(23). Recently, the use of 19 F-1D NMR to detect enzyme activity and inhibition both in proteases and kinases has been reported (22).…”
Section: Resultsmentioning
confidence: 99%
“…Although the fluorescence-based assay is a robust technique to search for very potent inhibitors, it becomes more ambiguous in detecting weaker ligands (Ͼ100 M), possibly due to interference introduced by test compounds (normally used at high concentration) in the spectrophotometric assay. For this reason, we relied on a NMR-based enzymatic assay, which is unlikely to lead to false positives (16)(17)(18)(19)(20)(21)(22)(23). Recently, the use of 19 F-1D NMR to detect enzyme activity and inhibition both in proteases and kinases has been reported (22).…”
Section: Resultsmentioning
confidence: 99%
“…We therefore conclude that the catalytic loop and the nicotinamide moiety of NADPH are simultaneously required for their correct positioning at the active site. A recent NMR study demonstrated the proximity of a methionine and an isoleucine residue to the nicotinamide ring portion of NADPH (41). Potential candidates at the active site are Met-214 or Met-276 and Ile-13 or Ile-218, respectively, which all represent almost strictly conserved residues.…”
Section: Binding Of Manganese and Fosmidomycin And Implicationsmentioning
confidence: 99%
“…Selective-labeling approaches have been used to measure intermolecular NOEs without the need for explicit side-chain assignment. [6] Ligandbased techniques, such as TrNOE [7] or TrCCR, [8] define the structure of a ligand in its protein-bound state but do not give information about its binding mode. Sometimes they even require isotope labeling of the ligand.…”
Section: Introductionmentioning
confidence: 99%